Implementasi Pendekatan Participatory Development Planning oleh Pemerintah Desa Setelah Diundangkannya Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Mirani Sucisia Dewi (CV Rewang Rencang, 2022)
Village Act regulates a participatory approach in the village development planning process, but normatively this provision is considered to conflict with Article 79 paragraph (1) which indirectly places villages as assistants for regional government affairs, thus giving the concept of pseudo-autonomy. Therefore, it is necessary to research the implementation of a participatory approach in village development planning after the enactment of the Village Act. The research was conducted using normative juridical methods. Based on the results of the study, it was concluded that the implementation of the participatory approach was hindered by the provisions of Article 79 paragraph (1) so it was necessary to renew the regulation regarding decision-making using a top-down and bottom-up approach together.